Simultaneous Inversion of Event m sub Lg and Path Attenuation Coefficient with Application to a Transportable Lg Magnitude Scaling - Jih, Rong-Song; Baumstark, R.; Wagner, R. (1995)
A simple, consistent, and transportable magnitude scale for regional phases is useful and often required in order to (a) improve the source discrimination capability, (b) determine the station detection threshold, and (c) estimate the explosive yield. A convenient, and hence recommended, magnitude formula for Lg phase is given. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p411-419.